TOWARDS A SOCIAL NICHE ASSESSMENT INSTRUMENT - Ryke, EH; Strydom, H; Botha, KFH (Social Work/Maatskaplike Werk, 2008)
From a social work perspective, individual outcomes are the results of a transactional process between personal and environmental influences. It is a long-cherished conviction in Social Work that individual problems and successes must be framed within the larger context of family, community and society (Saleebey, 2002c:231). However, it is also a conviction that is often not reflected in social work practice (Rose, 2000:405; Saleebey, 2002c:230; Weick, 2000:398). Clinical practice tends to focus on personal factors, and community practice on environmental factors, while the transactional dimension is often not accounted for. The tendency is also to focus on deficits and problems in these systems and not on strengths or potential strengths.